Usability measurement model of the human-robot interactive communication interface for human assistance tasks - Jimenez Moreno, Robinson; Espitia Cubillos, Anny Astrid; Rodríguez Carmona, Esperanza (LACCEI, 2024)
This article presents a statistical analysis, with non-parametric tests, of a model to identify the perception of various users regarding the usability of an interactive human-robot communication interface to assist people with specific tasks. Pre-recorded responses are used, keeping in mind the importance of communication between a robot and its user for the execution of tasks by voice commands, without room for errors in the interpretation of the different commands. The results allow us to see the independence between the variables and their percentage relationship, which indicates that the nominal variables proposed in the evaluation model are independent, so they must be included in their entirety. The model groups the nominal variables: clarity, assertiveness, naturalness, effectiveness, satisfaction, ease, usefulness and learning, in the three usability criteria proposed by the ISO 9241-11:2018 standard, namely: effectiveness, efficiency and user satisfaction